2009
DOI: 10.1038/nrneurol.2009.197
|View full text |Cite
|
Sign up to set email alerts
|

MGMT promoter methylation in malignant gliomas: ready for personalized medicine?

Abstract: The DNA repair enzyme O 6 -methylguanine-DNA methyltransferase (MGMT) antagonizes the genotoxic effects of alkylating agents. MGMT promoter methylation is the key mechanism of MGMT gene silencing and predicts a favorable outcome in patients with glioblastoma who are exposed to alkylating agent chemotherapy. This biomarker is on the verge of entering clinical decision-making and is currently used to stratify or even select glioblastoma patients for clinical trials. In other subtypes of glioma, such as anapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
498
1
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 671 publications
(550 citation statements)
references
References 87 publications
20
498
1
15
Order By: Relevance
“…Mo¨llemann et al (2005) reported that 1p/19q-deleted oligodendroglial tumours frequently demonstrate promoter hypermethylation and reduced expression of the O(6)-methylguanine DNA methyltransferase (MGMT) gene, an aberration that has been linked to response to TMZ therapy in glioblastoma patients (Hegi et al, 2005) as well as response to chemo-and radiotherapy in anaplastic glioma patients (Wick et al, 2009). However, although MGMT inactivation undoubtedly is of relevance for TMZ sensitivity (for review see Weller et al, 2010), a mechanistic role of MGMT in mediating radiosensitivity has not been demonstrated, thus suggesting the involvement of genetic/epigenetic alterations in other genes. Our in vitro results clearly demonstrate that not only TMZ-induced apoptosis is strongly (more than fivefold) increased after PRDX1 silencing in Hs683 cells, but they also show significantly higher sensitivity of PRDX1-knockdown Hs683 cells to ionizing irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Mo¨llemann et al (2005) reported that 1p/19q-deleted oligodendroglial tumours frequently demonstrate promoter hypermethylation and reduced expression of the O(6)-methylguanine DNA methyltransferase (MGMT) gene, an aberration that has been linked to response to TMZ therapy in glioblastoma patients (Hegi et al, 2005) as well as response to chemo-and radiotherapy in anaplastic glioma patients (Wick et al, 2009). However, although MGMT inactivation undoubtedly is of relevance for TMZ sensitivity (for review see Weller et al, 2010), a mechanistic role of MGMT in mediating radiosensitivity has not been demonstrated, thus suggesting the involvement of genetic/epigenetic alterations in other genes. Our in vitro results clearly demonstrate that not only TMZ-induced apoptosis is strongly (more than fivefold) increased after PRDX1 silencing in Hs683 cells, but they also show significantly higher sensitivity of PRDX1-knockdown Hs683 cells to ionizing irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods for MGMT expression analysis, e.g., by Western blot analysis 28 or a quantitative PCR, were not addressed here but may be similarly confounded by the presence of non-neoplastic cells in the tumor tissue. 4,7 Role of aberrant MMR genes in recurrent glioblastomas Several studies have suggested a role of MMR gene alterations in the resistance to TMZ and glioblastoma relapse. Friedman et al 8 demonstrated involvement of MSH2 deficiency in the methylator resistance of a human glioblastoma xenograft.…”
Section: Clinical Implications For Mgmt Promoter Methylation Testingmentioning
confidence: 99%
“…Aberrant MGMT promoter methylation may lead to transcriptional repression and lower MGMT protein expression in tumor cells, which may explain the clinical association of MGMT promoter methylation with longer survival of TMZ-treated glioblastoma patients. 4 Nevertheless, virtually all glioblastomas relapse after the initial therapy, including the best prognostic subgroup of completely resected and MGMT promoter-methylated tumors. 7 The molecular mechanisms underlying therapy resistance and recurrence of glioblastomas are still unclear.…”
mentioning
confidence: 99%
“…Tumor cells expressing MGMT are resistant to alkylating agents, while those that lack the DNA-repair protein are more susceptible. In most cases, the silencing of MGMT is associated with methylation of the promoter [13]. Here, we observed that the MGMT promoter is methylated in sperm and that temozolomide treatment does not alter this pattern.…”
Section: Discussionmentioning
confidence: 51%